Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Bank Resolution and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2020)
This technical note on Austria focuses on bank resolution and crisis management. This note assesses and makes recommendations regarding bank resolution and crisis management arrangements. The scope of the assessment includes the institutional arrangements for recovery, resolution, and crisis management; the supervision of banks' recovery plans; the legal regime for bank bankruptcy and resolution; resolution planning by the authorities and addressing impediments to resolution; assuring funding to support resolution; the two deposit guarantee schemes; and the government authorities' collective preparedness to deal with financial crisis. Recovery and resolution planning are well advanced. Key impediments to resolution have been identified and are being addressed, yet adequate means to ensure enough funding in resolution remains to be determined. The legal framework is sound, although additional flexibility could be provided in the bankruptcy regime. The authorities' collective contingency planning for financial crisis and testing of plans should be intensified.